Islamic banking & finance in South-East Asia : its development & future - Venardos, Angelo M. (Asia-Pacific business series ;, 2006)
To truly understand the current interest in the development of Islamic banking and finance in South-East Asia and how it is different from the conventional banking system, one must first understand the religious relationship originating from the Qur'an, and then trace the historical geographic and political developments of Islam over recent centuries. Only on this basis can the reader, without prejudice or cynicism, begin to appreciate Shari'ah law and Islamic jurisprudence. With this platform established in the first part of the book, readers are invited to learn about the financial products.